Combining intensive counseling by frontline workers with a nationwide mass media campaign has large differential impacts on complementary feeding practices but not on child growth: Results of a cluster-randomized program evaluation in Bangladesh - Menon, Purnima; Nguyen, Phuong Hong; Saha, Kuntal K.; Khaled, Adiba; Sanghvi, Tina; Baker, Jean; Afsana, Kaosar; Haque, Raisul; Frongillo, Edward A.; Ruel, Marie T.; Rawat, Rahul (Elsevier, 2016)
**Background**: Complementary feeding (CF) contributes to child growth and development, but few CF programs are delivered at scale. Alive & Thrive addressed this in Bangladesh through intensified interpersonal counseling (IPC), mass media (MM), and community mobilization (CM).